Factores que inciden en la participación de los artesanos del cantón Bolívar en la contratación pública - Bravo Bravo, Virginia Lizeth (2025)
The present research aimed to analyze the factors that influence the participation of artisans from Bolívar canton in public procurement processes, in order to increase their involvement in such procedures. Consequently, the study was developed in three phases aligned with the specific objectives. Initially, the legal framework of Public Procurement processes was described to identify the participation of local artisans, applying deductive and analytical–synthetic methods, as well as bibliographic research. Subsequently, interviews were conducted with the head of the Citizen Participation Department and the president of the Interprofessional Association of Artisans and Operators of Bolívar canton. Additionally, a survey based on a Likert scale was administered to local artisans through Google Forms. Based on the results obtained, an improvement plan was designed and later presented to the corresponding artisans and operators. The collected information revealed a general lack of knowledge regarding public procurement procedures and the complexity of their requirements, limited engagement of artisans in these processes, and poor awareness of the legislation intended to protect and promote their rights, among other factors. In conclusion, this study highlights the importance of fostering artisans’ participation in Public Procurement as a means to promote the economic and social development of the inhabitants of Bolívar canton.